2021
DOI: 10.1177/0040517521994678
|View full text |Cite
|
Sign up to set email alerts
|

Testing the effects of fabrication parameters on the post-fabrication shape change of a three-dimensional printed textile platform

Abstract: In this study, a moisture-stimulated three-dimensional printing filament was printed onto an elastic band. The created textile platform changes its shape permanently after exposure to a high-moisture environment. Three main manufacturing parameters – that is, the printed pattern’s infill percentage, the printed pattern’s thickness, and the textile stretch – were tested to study their effects on the platform curving process. It was observed that an increase of the printed pattern’s infill density from 20% to 80… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…Additionally, we did not assess the impact of infill patterning on the mechanical strength of these scaffolds. However, our previous work [ 22 , 27 ] showed that LAY-FOMM60 is quite elastic with significantly lower mechanical strength than PLA, which is in agreement with other mechanical testing of these materials [ 29 , 30 , 31 ]. Even though this material was able to promote bone repair in a mandible defect, this would have to be considered for load bearing applications and regeneration in large bone defects.…”
Section: Discussionsupporting
confidence: 86%
“…Additionally, we did not assess the impact of infill patterning on the mechanical strength of these scaffolds. However, our previous work [ 22 , 27 ] showed that LAY-FOMM60 is quite elastic with significantly lower mechanical strength than PLA, which is in agreement with other mechanical testing of these materials [ 29 , 30 , 31 ]. Even though this material was able to promote bone repair in a mandible defect, this would have to be considered for load bearing applications and regeneration in large bone defects.…”
Section: Discussionsupporting
confidence: 86%
“…Three-dimensional printing is a 3D technology that completes objects in three dimensions, providing more freedom in design that enables complex structures. [1][2][3] It is also easy to produce small quantities of various and customized products, which can increase the efficiency of costs by making individual customized parts. 4 Thus, as 3D printing technology and materials are further developed and the distribution of personal fused deposition modeling (FDM) methods accelerates, expectations for expanding the market for the convergence and complexity of 3D printing technology and materials are increasing.…”
Section: D Printing and Methodsmentioning
confidence: 99%
“…Dimensional stability describes the dimensional change that occurs in the length or width direction when the fabric is subjected to higher temperatures. 44 Dimensional stability affects the service life of the fabric and is an important quality indicator of the garment. 45 The dimensional stability analysis of the sample is shown in Table 5.…”
Section: Dimensional Changesmentioning
confidence: 99%